MSL Framework: (Minimum Service Level Framework) for Cloud Providers and Users - Khan, Sohail (2017)
Cloud Computing ensures parallel computing and emerged as an efficient technology to meet the challenges of rapid growth of data that we experienced in this internet age. Cloud computing is an emerging technology that offers subscription based services, and provide different models such as IaaS, PaaS and SaaS to cater the needs of different users groups. The technology has enormous benefits but there are serious concerns and challenges related to lack of uniform standards or nonexistence of minimum benchmark for level of services across the industry to provide an effective, uniform and reliable service to the cloud users. As the cloud computing is gaining popularity organizations and users are having problems to adopt the service due to lack of minimum service level framework which can act as a benchmark in the selection of the cloud provider and provide quality of services according to the users expectations. The situation becomes more critical due to distributed nature of the service...